Dispute Settlement of Regional Head General Election Results On the Difference in Voting; Analysis of the Decision of the Constitutional Court No.28/PHP.BUP-XVI/2018 Regarding the Determination of the Regional Head of Bogor Regency 2018 - Muhammad Latief; Siti Ngainnur Rohmah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The dissatisfaction of the Bogor Regency Regent and Deputy Regent candidates caused the Jaro Ade-Inggrid Kansil pair to sue the Bogor KPUD at the Constitutional Court. After carrying out the trial by examining the evidence and listening to witnesses, the Constitutional Court issued a shocking decision. In the decision of the Constitutional Court Number 28/PHP.BUP-XVI/2018, the Constitutional Court considered that Article 158 paragraph (2) letter d of the Pilkada Law stated that the determination of the results of the vote count with the provisions of districts/cities with a population of more than 1,000,000 people, Disputes over the acquisition of votes can be made if there is a difference of at most 0.5 percent of the total valid votes from the final stage of vote counting for Regency/Municipal KPU. This study uses a literature review research method with a legal approach, namely research on legal products. After being researched, it was found that the dispute resolution process of the post-conflict local election results was in accordance with the judicial procedural law at the Constitutional Court.